Groundwater Identification Employing Electromagnetic Very Low Frequency (EM-VLF) Technology for Drought Mitigation in Keben Village, Tambakromo District, Pati Regency, Central Java Province - Khakhim, Nurul; Adji, Tjahyo Nugroho; Febriarta, Erik (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Groundwater potential can be effectively assessed through geophysical surveys utilizing the Very Low Frequency (VLF) electromagnetic method. This technique employs low-frequency electromagnetic waves (15–30 Mhz) to detect subsurface conductive lithologies indicative of groundwater presence. This study, conducted in Bugel Hamlet, Keben Village, Tambakromo District, Pati Regency, Central Java, aimed to delineate the spatial distribution and depth of potential groundwater resources. The region faces intensifying drought conditions; in 2023, the affected population rose from 26,791 to 37,114. Furthermore, Tambakromo presents complex geological challenges, with lithology dominated by consolidated rocks (claystone, marl, and sandstone) of the Lidah and Mundu Formations. Consequently, existing aquifer systems exhibit low productivity and limited discharge rates (< 5 liters/second) due to the impermeability of the host rocks. VLF measurements revealed conductive anomalies at depths ranging from 26.4 to 60 meters, suggesting the presence of a potential aquifer. This layer is interpreted as coarse-grained sandstone intercalated with clay, overlying a claystone bedrock. Based on this interpretation, specific coordinates were recommended for drilling. The study concludes that the Bugel area possesses a minimum groundwater potential of 3,500 liters per hour with good water quality and a dissolved solids content of 24%. Drilling at the recommended site yielded coarse sand, confirming the existence of an unconsolidated aquifer with high porosity and sustainable reserves. Project sustainability relies on collaboration between the village administration and the local farming community. Future development plans propose storing extracted water in reservoirs for distribution via piping systems to irrigate agricultural land, thereby breaking the cycle of annual water crises and enhancing local economic resilience.